2019
DOI: 10.1063/1.5097285
|View full text |Cite
|
Sign up to set email alerts
|

Multirotor wind turbine wakes

Abstract: To fulfill the increasing need for large power generation by wind turbines, the concept of multi-rotor wind turbines has recently received attention as a promising alternative to conventional massive single-rotor wind turbines. To shed light on the viability of this concept, large-eddy simulation is employed in this study to compare wake flow properties of a multi-rotor wind turbine with those of a single-rotor turbine. The wake of a multi-rotor turbine is found to recover faster at short downwind distances, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 49 publications
5
29
0
Order By: Relevance
“…The analytical model employed is an extension of the Gaussian wake model developed by Bastankhah and Porté‐Agel, 9 which was initially developed for single yawed rotors. In the case of a multirotor turbine, such as that illustrated in Figure 3A, the Gaussian wake model is applied to each rotor, and the individual wakes are then linearly superposed as suggested by Bastankhah and Abkar 46 . For the n th yawed rotor, the individual wake widths in the lateral and vertical directions, respectively, can be found by {leftarrayσynd=knxx0d+cosγn8,arrayσznd=knxx0d+18, where k n is the wake growth rate associated with each rotor, which is assumed to be equal in lateral and vertical directions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analytical model employed is an extension of the Gaussian wake model developed by Bastankhah and Porté‐Agel, 9 which was initially developed for single yawed rotors. In the case of a multirotor turbine, such as that illustrated in Figure 3A, the Gaussian wake model is applied to each rotor, and the individual wakes are then linearly superposed as suggested by Bastankhah and Abkar 46 . For the n th yawed rotor, the individual wake widths in the lateral and vertical directions, respectively, can be found by {leftarrayσynd=knxx0d+cosγn8,arrayσznd=knxx0d+18, where k n is the wake growth rate associated with each rotor, which is assumed to be equal in lateral and vertical directions.…”
Section: Methodsmentioning
confidence: 99%
“…Such power increases are primarily seen as a result of faster wake recovery in the range of 5–8 rotor diameters, which is the typical streamwise turbine spacing for most wind farms. Bastankhah and Abkar 46 found that this was due to individual rotor wakes remaining distinct in this range, where at greater distances they merge to form a single wake. LES studies of Ghaisas et al 47 also demonstrated lower wake losses, which was linked to a higher planform energy flux and greater flow entrainment in the wake.…”
Section: Introductionmentioning
confidence: 98%
“…To better quantify the influence of VAWTs on the energy extraction from the turbulent incoming flow, a budget analysis of the mean kinetic energy for the wake flows through the wind farm is performed. As shown in previous studies [33][34][35], this analysis can shed light on the physics of energy exchanges between the incoming flow and turbine wakes. Under the steady-state condition, the kinetic energy budget of the mean flow can be written as where the overbar shows temporal averaging, ũ i = ũi − ūi .…”
Section: Kinetic Energy Budgets Of the Mean Flowmentioning
confidence: 55%
“…Constraining As=Am0.1emn reduces the blade radius for the MRWT to Rm=Rn where R is the SRWT rotor radius which makes the power scaling between an SRWT and an MRWT equal; however, the mass scaling of the torque driving components favors the MRWT by the factor 1n 13 . Test studies and numerical simulations of MRWT have also shown an increased power production and more compact spacing capabilities compared to SRWT 14,15 . The drawbacks of the MRWT concept compared to an SRWT include higher maintenance cost, a more challenging installation procedure, and increasing complexity of the structure supporting the multiple rotors.…”
Section: Introductionmentioning
confidence: 99%